Implementasi Kebijakan Green Cleaning Pada Villa Di Kawasan Wisata Kabupaten Gianyar Bali - Sunarsa, I Wayan; Seniartha, I Wayan; Sekarti, Ni Ketut; Darmaputra, Putu Gede Eka (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
This is a new author guidelines and article template of JIP (Jurnal Ilmiah Pariwisata ). Article should be This research aims to determine the implementation of green cleaning policies in villas in the tourist area of ​​Gianyar district Bali. This research is qualitative research with a case study approach. The number of samples is 15 villas in the tourist area of ​​Gianyar district. Data collection methods were carried out by interviews, observation and documentation. The informant is the executive housekeeper as head of the Housekeeping department. The research results show that of the 10 aspects of green cleaning that have been determined, 75.7% have been carried out and articulated well by villa entrepreneurs in the tourist area of ​​Gianyar district.